A-site deficient chromite with in situ Ni exsolution as a fuel electrode for solid oxide cells (SOCs). Issue 9 (5th February 2021) - Amaya-Dueñas, Diana-María; Chen, Guoxing; Weidenkaff, Anke; Sata, Noriko; Han, Feng; Biswas, Indro; Costa, Rémi; Friedrich, Kaspar Andreas
Abstract : A -site deficient chromite La0.65 Sr0.3 Cr0.85 Ni0.15 O3− δ (L65SCrN) decorated by in situ Ni exsolution was implemented as fuel electrode on 5 cm × 5 cm reversible electrolyte-supported solid oxide cells (rSOCs). Abstract : A -site deficient lanthanum strontium chromite perovskite La0.65 Sr0.3 Cr0.85 Ni0.15 O3− δ (L65SCrN) decorated by in situ exsolution of Ni nanoparticles was synthesized and implemented as a fuel electrode on a 5 cm × 5 cm electrolyte-supported cell (ESC) for solid oxide cells (SOCs) with an active surface of 16 cm 2 . The stoichiometric formulation La0.70 Sr0.3 Cr0.85 Ni0.15 O3− δ (L70SCrN) was also prepared in order to evaluate the reducibility and behavior towards Ni exsolution with respect to L65SCrN. This comparison was assessed by means of X-ray diffraction (XRD) and thermogravimetric analysis (TGA) in a reducing atmosphere. Metallic Ni was successfully detected using XRD on the A -site deficient formulation after TGA treatment. Surface analysis by means of X-ray photoemission spectroscopy (XPS) revealed a relative enrichment in Cr 3+ . Ni exsolution was investigated on the L65SCrN formulation by annealing in a reducing atmosphere at 500 °C and 900 °C for 3 hours. The Ni nanoparticle size (from ∼8 up to 100 nm) and morphology were characterized by means of scanning electron microscopy (SEM). Furthermore, L65SCrN was screen printed onto a 90 µm thick CGO20-3YSZ-CGO20 electrolyte on which the oxygen electrode La0.58 Sr0.4 Fe0.8 Co0.2 O3− δ (LSCF) was printed on the other side. With ideal contacting, the electrochemical cell performance of the L65SCrN fuel electrode was demonstrated to be comparable to those of the state-of-the-art Ni-based cermets: ASRDC_Total at −0.3 A cm −2 was calculated to be 0.676 Ω cm 2 in co-electrolysis operation. Reversible operation (rSOC) at 860 °C with a H2 O/H2 ratio of 1 could be shown and co-electrolysis operation (H2 O/CO2 = 2) at −0.45 A cm −2 and 860 °C with a voltage degradation of less than 3.5 mV/1000 hours could be demonstrated for 950 hours. Even though L65SCrN showed promising results for SOC operation, further investigations of Ni exsolution in doped chromites by varying temperature, time and p O2 are proposed for a detailed understanding and optimization of the Ni nanoparticle size.